1990
DOI: 10.1002/zaac.19905910105
|View full text |Cite
|
Sign up to set email alerts
|

(CN)ONa3, Kristallstruktur und Natriumionenleitfähigkeit

Abstract: Einkristallstrukuruntersuchungen zufolge leitet sich die Kristallstruktur von Na3O(CN)=(CN)ONa3 vom Antiperowskittyp ab (a = 454,3(1) pm, Pm3m); das Cyanidanion ist fehlgeordnet. Oberhalb von 230°C ist Na3O(CN) ein schneller Natriumionenleiter. Die hohe Natriumionenbeweglichkeit resultiert zum einen aus der Rotationsdiffusion des CN−‐Anions (Drehtüreffekt) und zum anderen aus dem Teilschmelzen der Kationenstruktur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 8 publications
1
20
0
2
Order By: Relevance
“…We noticed two previous reports on the ionic conductivity of antiperovskite Na 3 OBr and Na 3 OCN gave low values below their melting points [28,29]. In the present work, we demonstrated that both A-site size-mismatch substitution and unequivalent alkali-earth-metal doping could improve the ionic conducting performance remarkably.…”
Section: Sodium Ionic Conductivitysupporting
confidence: 50%
“…We noticed two previous reports on the ionic conductivity of antiperovskite Na 3 OBr and Na 3 OCN gave low values below their melting points [28,29]. In the present work, we demonstrated that both A-site size-mismatch substitution and unequivalent alkali-earth-metal doping could improve the ionic conducting performance remarkably.…”
Section: Sodium Ionic Conductivitysupporting
confidence: 50%
“…The variants obtained, like (NO,),ONa, (Fig, 6), are to be assigned the anti-K,NiF, structure, or like (CN)ONa, contain another disordered anion in place of NO; .I3', 33] The close relationship of these compounds is underscored by the mutual solubility[341 of BrONa,t351 and (NO,)ONa,.…”
mentioning
confidence: 98%
“…Therefore, the CN anions have to be either dynamically or statically disordered over six equivalent orientations, so that a volume and/or time average gives a cubic space group. 15 Contrary to the pure alkali cyanides, no temperature-induced phase transition has been observed in the temperature range from ambient conditions down to 120 K. As the observed atomic displacement factors of C and N were small, static disorder has been assumed. 15 The local symmetry breaking by static disorder raises the question of how the structure responds locally.…”
Section: Introductionmentioning
confidence: 96%
“…14 In contrast to the multitude of studies carried out on alkali cyanides, only few studies have been directed to understand whether trialkali oxide cyanides, where the structural aspects are quite similar, show a related behavior. According to single-crystal x-ray structure determinations Na 3 O͑CN͒ 15 and K 3 O͑CN͒ 16 crystallize in the antiperovskite structuretype with space group symmetry Pm3m (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%